Proteins Pre-concentration Using Glycidyl Methacrylate-co-stearyl Methacrylate-co-ethylene Glycol Dimethacrylate Monolith - Ahmed Ali Alkarimi; Kevin Welham (Indonesian Journal of Chemistry, 2020)
Solid-phase extraction technique is considered as a vital tool in a pre-treatment of different samples. Therefore, it was used as a beneficial and alternative extraction method over the liquid–liquid extraction in diverse applications such as food, environmental, and biological analyses. Glycidyl methacrylate-co-stearyl methacrylate-co-ethylene glycol dimethacrylate (GMA-co-SMA-co-EDMA) monolithic sorbent was prepared as strong cationic-reversed phase sorbent for solid-phase extraction of different proteins. The monolithic sorbent was prepared inside two moulds such as glass microchip device and borosilicate. The morphological properties have been investigated using the Brunauer-Emmett-Teller (BET) model analyzer and scanning electron microscope (SEM), and the formation of the monolithic sorbent was examined using the FT-IR. Eight proteins (cytochrome C, insulin, myoglobin, lysozyme, β-lactoglobulin, trypsin, albumin chicken egg white, and apo-transferrin) with different molecular weight and isoelectric point were investigated for pre-concentration using the SCX/RP sorbent. It was found that the highest extraction recovery was obtained with three proteins cytochrome C, lysozyme, and myoglobin compared with the other proteins. These three proteins were chosen for pre-concentration using the glass microchip. Sorbent performance showed significant results in terms of stability and reproducibility.